Advancing Problem-Solving Competencies in Prospective Science Teachers: Comparative Insights on the Flipped Classroom and Direct Instruction Models - I Made Sutika; Ni Made Pujani; Ketut Suma; Putu Hari Sudewa (Universitas Pendidikan Ganesha, 2024)
Improving problem-solving skills is a key challenge in science education. Traditional models like Direct Instruction (DI) often limit student engagement, prompting the need for innovative approaches such as the Flipped Classroom (FC) model. This study aims to analyze differences in problem-solving skills between students taught using the FC model and those taught using the DI model. This quasi-experimental research employed a non-equivalent pretest-posttest control group design. The sample, consisting of 34 fourth-semester prospective science teachers, was selected through random sampling. The experimental group (FC model) and control group (DI model) each included 17 students. Problem-solving skills were assessed using an essay test in a biophysics course, with a reliability coefficient of 0.717. Data were analyzed descriptively and using ANCOVA at a 5% significance level. The results showed medium improvements in problem-solving skills for both groups, with N-gains of 64.30 for the FC model and 32.94 for the DI model. A significant difference was found between the groups (p < 0.05), with students in the FC group achieving higher problem-solving scores. In conclusion, the FC model is more effective in enhancing problem-solving skills compared to the DI model. Active learning strategies in the FC model foster deeper engagement, supporting the development of essential cognitive skills in science education.